Characterization of Patients with Ischemic Cerebrovascular Disease Treated at the Guillermo Dominguez General Teaching Hospital in Las Tunas - Yurieski Pérez Velázquez; Alián Pérez Marrero; Alberto Caballero Laguna (Revista Finlay)
Background: cerebrovascular diseases are a global health problem and one of the main causes of mortality and global disability. Objective: to clinically characterize patients with ischemic cerebrovascular disease admitted to the Internal Medicine Service of the Guillermo Domínguez López General Teaching Hospital in the period between May 2019 and May 2021. Method: a descriptive cross-sectional study was carried out in the Internal Medicine Service of the Guillermo Domínguez López General Teaching Hospital in the Puerto Padre municipality in Las Tunas province in the period between May 2019 and May 2021. The study population consisted of 184 patients diagnosed with ischemic cerebrovascular disease. The sample coincided with the universe when studying the total number of patients. The following variables were characterized: age, sex, risk factors, clinical forms of presentation, complications, and survival to discharge. Descriptive statistics were used. The results were presented in frequency distribution tables for better understanding and analysis. Results: male patients (53.80 %) and the age group of 65 to 74 years with 33.15 % predominated. The main risk factor was arterial hypertension (58.29 %) and atherothrombotic cerebral infarction prevailed with 47.83 % as the clinical form of presentation. Respiratory infections (28 %) were the ones with the highest incidence in terms of complications. 92.93 % of the patients were discharged alive. Conclusions: hypertensive patients over sixty years of age, admitted with atherothrombotic cerebral infarction, predominated.